PURITY & PROFILE MATCHING APPROACH TO DETERMINE THE GOVERNMENT AID RECIPIENT IN ACEH UTARA, INDONESIA - Sujacka Retno; Novia Hasdyna (INFOKUM, 2022)
Purity algorithm is a new algorithm in the field of informatics that used to measure the pure value of a number of data. Profile Matching algorithm is an algorithm that used in making a decision, such as determining the criteria for receiving aid from the government. This research aims to apply the two algorithms, Purity & Profile Matching in determining the criteria of recipients for government aid funds for citizens in Aceh Utara in 2022, where it is hoped that the funds will be accurately given to people in need. The criterias used in this research include name, occupation, income, assets, and number of dependents. The data that has been collected then analyzed by applying the Purity & Profile Matching algorithm. As for this research, two methods will be applied namely Purity & Profile Matching. It used as a comparison in determining the criteria needed in determining the acceptance of the aid funds. This research applied to a Web-based system using the PHP programming language and MySQL database.